2019
DOI: 10.1182/blood-2019-124631
|View full text |Cite
|
Sign up to set email alerts
|

The Chronic Lymphocytic Leukemia Comorbidity Index (CLL-CI): A Novel Comorbidity Score Derived from a Large Multicenter Retrospective Cohort Study of Patients Treated with Ibrutinib and/or Chemo-Immunotherapy (CIT)

Abstract: Introduction: Outcomes in CLL are highly variable and influenced by both biologic and clinical factors. The Cumulative Illness Rating Scale (CIRS) is frequently used to assess comorbidities in CLL. Our group has demonstrated that CIRS correlates with survival in patients treated with either CIT or ibrutinib. Yet, CIRS has not become part of common clinical practice due to complexities in scoring since 14 systems need to be evaluated. Furthermore, the relative contribution of individual comorbidities to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…They also found that hypertension and cardiac comorbidities did not improve CLL-CI’s discriminatory power. 48 Even in our series, cardio-comorbidities did not affect survival outcomes, possibly because of an a priori exclusion and accurate selection of patients before starting ibrutinib treatment.…”
Section: Discussionmentioning
confidence: 56%
“…They also found that hypertension and cardiac comorbidities did not improve CLL-CI’s discriminatory power. 48 Even in our series, cardio-comorbidities did not affect survival outcomes, possibly because of an a priori exclusion and accurate selection of patients before starting ibrutinib treatment.…”
Section: Discussionmentioning
confidence: 56%
“…Generally, patients with comorbidities do not respond as well to treatment as those without, and comorbidities, including musculoskeletal and endocrine problems, confer inferior outcomes in patients treated with ibrutinib. 44,77 However, this is yet to be evaluated in patients treated with acalabrutinib.…”
Section: Considerations For Treating Patientsmentioning
confidence: 99%
“…Before administration, a baseline medical history must be taken, including recent surgery/plans for surgery; history of cardiac arrhythmias; hypertension; infections (including history of hepatitis B virus infection); and current medications, including prescription, over‐the‐counter medicines and, importantly, herbs and supplements. Generally, patients with comorbidities do not respond as well to treatment as those without, and comorbidities, including musculoskeletal and endocrine problems, confer inferior outcomes in patients treated with ibrutinib 44,77 . However, this is yet to be evaluated in patients treated with acalabrutinib.…”
Section: Acalabrutinib: Clinical Usementioning
confidence: 99%
“…Interestingly, neither cardiac disease nor hypertension were factors strongly associated with shortened survival in these patients. 60 While it may be intuitive that patients with comorbidities have worse outcomes with oncologic drug treatments, we have also shown that comorbidities have minimal impact on idelalisib therapy. 61 This further justifies exploration of the role of comorbidities in patients treated with second-generation BTK inhibitors.…”
Section: Something Blue: Challenges With Btk Inhibitionmentioning
confidence: 81%